PENGUKURAN NARSISME CEO DALAM PENELITIAN DI BIDANG BISNIS, MANAJEMEN DAN AKUNTANSI: SEBUAH STUDI LITERATUR - Kadek Ernawan; Debby Ratna Daniel (Universitas Medan Area, 2020)
This study is objected to discussing a literature review that challenges and trends of CEO narcissism measurement study in the field of business, management and accounting.The literatures were obtained from search results in the scopus and google scholar database. This research successfully identified and analyzing by using netha analysys of 212 articles during the period 2009-2019 and found 33 articles that discussed CEO’s narcissism in business, management and accounting study. This study found six narcissism measurements used in the fields of business, management and accounting study. Six narcissism measurements are narcissistic personality inventor (NPI), gough adjective check list (ACL), five indicators of narcissism Chatterjee & Hambrick (2007), fifteen indicators of narcissism Rijsenbilt (2011), LinkedIn Aabo & Eriksen (2018) measurement and CEO’s signature size.